2013
DOI: 10.1074/jbc.m113.494534
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of Differentiation 38 (CD38) Mediates Bile Acid-induced Acinar Cell Injury and Pancreatitis through Cyclic ADP-ribose and Intracellular Calcium Release

Abstract: Aberrant Ca2+ signals within pancreatic acinar cells are an early and critical feature in acute pancreatitis, yet it is unclear how these signals are generated. An important mediator of the aberrant Ca2+ signals due to bile acid exposure is the intracellular Ca2+ channel ryanodine receptor. One putative activator of the ryanodine receptor is the nucleotide second messenger cyclic ADP-ribose (cADPR), which is generated by an ectoenzyme ADP-ribosyl cyclase, CD38. In this study, we examined the role of CD38 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Many studies found that Ca++ is overloaded in pancreatic acinar cells [17] , the sustained calcium elevation activates intracellular digestive proenzymes which leads to necrosis and toxicity [18] – [20] , resulting in necrosis and inflammation in AP [21] , [22] . Based on these previous findings, in the present study we did not focus on examining the calcium content in the pancreatic acinar cells in the pancreatic tissue of AP using animal experiments, but rather focused on investigating the relationship between the miRNAs and the calcium expression.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that Ca++ is overloaded in pancreatic acinar cells [17] , the sustained calcium elevation activates intracellular digestive proenzymes which leads to necrosis and toxicity [18] – [20] , resulting in necrosis and inflammation in AP [21] , [22] . Based on these previous findings, in the present study we did not focus on examining the calcium content in the pancreatic acinar cells in the pancreatic tissue of AP using animal experiments, but rather focused on investigating the relationship between the miRNAs and the calcium expression.…”
Section: Discussionmentioning
confidence: 99%
“…To stimulate AP in vitro , AR42J cells were treated with 500 μM of Na‐TC based on previous reports and our preliminary experiments. For control group, the cells were treated with an equivalent volume of PBS to that of Na‐TC administrated in AP group.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that pharmacologic blockade of CD38 and cADPR could be a therapeutic option in biliary pancreatitis. 96 Calcineurin inhibitory peptide was added to prevent BA-induced acinar cell injury because TLCS is able to cause calcineurin activation. Finally, the calcineurin inhibitors limited chymotrypsinogen activation.…”
Section: Potential Beneficial Effects Of Bas and Targeted Treatment Imentioning
confidence: 99%